Membangun Kesadaran Lingkungan Melalui Pendidikan Kewarganegaraan di Sekolah Dasar - Sunaryati, Titin; Rahmawati, Alfi; Adinda, Aya Dea; Z, Alya Aulya Zakyyatuz; Qolby, Cut Rafa Auliya (LPPPI Publishing, 2024)
Citizenship education plays an essential role in developing children's character, in line with moral, character and character education. This program aims to produce good citizens based on the values ??of Pancasila, which is the culture of the Indonesian nation. Building environmental awareness through citizenship education in elementary schools is very important, because it helps students understand their responsibilities towards the environment. The five principles of Pancasila are basic values ??that have developed into instrumental and rational values, creating a generation that cares about others and preserving nature. This research method uses a qualitative approach with literature study, collecting data from various relevant literature such as books, journals and official documents related to education citizenship in Indonesia. The data collection process began with a literature review through academic databases such as Google Scholar and JSTOR, followed by literature selection based on inclusion and exclusion criteria. The data is then categorized according to themes to produce an in-depth understanding of this topic. Civic education lessons have an important role in building environmental awareness by introducing the concepts of citizens' rights and obligations and environmental protection. Although there are challenges in integrating environmental education, there are opportunities to develop environmentally caring characters in students. Therefore, it is important to instill environmental awareness from an early age in everyday life, both at school and outside school.